Investigating the exchange of CO₂ in a tall-grass prairie ecosystem using stable isotopes and micrometeorological methods - Stropes, Kyle Scott (Kansas State University, 2017)
Isotope analysis combined with micrometeorological techniques can bring new insights into the mechanisms governing biogeochemical cycles in ecosystems. New field-deployable optical sensors that have recently become available can provide accurate trace gas concentration measurements at sampling rates suitable for micrometeorological measurements. These instruments could help enhance current carbon cycling research efforts. This research will bring new insights into understanding the biophysical processes governing the carbon cycle at the ecosystem scale, which will be crucial for enhancing our future climate change scenario predictions. The impact that land use management has on the carbon cycle components of an ecosystem is an important issue that could be addressed with this new approach. More notably, research is needed to identify how management practices affect the abundance of C₃ and C₄ plant communities in grasslands and to identify how shifts in plant community composition can modify the net ecosystem exchange of CO₂. Chapter 1 of this thesis provides a literature review on the carbon cycle in grasslands, stable isotope analysis in environmental mediums, and the combination of isotope analysis with micrometeorological methods to study carbon exchange at the ecosystem scale. In Chapter 2, we describe the evaluation of the performance for a multi-port sampling system’s measurements of vertical concentration gradients of stable isotopes of CO₂. The results of these analyzes show that the sampling system was suitable to measure vertical gradients of concentration under field conditions. Chapter 3 describes how the sampling system was used to study the isotope exchange in two watersheds at the Konza Prairie Biological station under distinct management conditions. Gradients of isotopes were measured in two adjacent watersheds (K2A and C3SA). The K2A watershed is burned every other year, while the C3SA watershed is in a patch-burn grazing system and is burned every three years. Results show that the sampling system’s performance is adequate for our study. The sampling system was able to detect clear differences in the isotopic composition of nighttime NEE between the watersheds, which is believed to be greatly influenced by C₃ and C₄ plant community composition. Further research is needed to examine the role that other environmental conditions played on altering the isotopic signals of the NEE in each watershed. Additionally, other management practices should be examined using this sampling system to determine their impact on biophysical drivers in the ecosystem, which could subsequently impact the plant community abundance and diversity.
Keywords: Micrometeorology; Isotope analysis; Atmospheric sciences; Meteorology; Carbon cycle; Land use management